Capital Punishment in China: Towards Effective Public Policy and Law - Jiang, Lilou (Université d'Ottawa / University of Ottawa, 2020)
Based on an examination of the rationality and moral legitimacy of capital punishment in China, this research depicts the evolution of the Chinese death penalty law and policy from 1979 onwards; investigates the institutional and procedural shortcomings that lead to pre-trial torture, wrongful convictions, and executions of innocent or vulnerable people; and explores the prospects for restricting the application of the death penalty in retentionist China by focusing on feasible legal and policy changes to assure fair trials in capital cases. The key research questions to be addressed are: why capital punishment persists in China in an age of abolition; and if the abolition cannot be achieved in the foreseeable future, what reforms should be introduced to prevent miscarriage of justice? This research finds that the Confucian theory of punishment constitutes a compelling unified theoretical framework and establishes solid philosophical and ethical foundations for the introduction and persistence of capital punishment in China. Responding to the concerns expressed by and pressure from the international human rights community together with domestic calls for more caution in meting out capital punishment, China has launched a series of reforms in the death penalty regime since the middle of 2000’s which has resulted in a significant reduction in the use of the death penalty. However, it is also observed that: capital offenders with mental illness are at a substantial disadvantage in receiving psychiatric assessment and thus are at a high risk of being sentenced to death; police ill-treatment and torture are rampant due to the deeply-rooted presumption of guilt and the confession-oriented approaches predominantly employed in police investigation practices; and the procedural loophole that suspended death sentence, although being a form of capital punishment, is not subject to review and final approval by the highest judicial authority has in effect condoned arbitrary sentencing in capital cases and consequently exacerbated the miscarriages of justice. It is concluded that the retention of capital punishment in China may be more impervious to abolitionists’ claims than other jurisdictions; hence, to improve its state competence in securing criminal justice, China should promote institutional and procedural changes in line with international human rights standards for protecting the rights of offenders facing the death penalty.
Keywords: Capital Punishment; Confucianism; Torture; Wrongful Convictions; China